Biomechanical model for evaluation of pediatric upper extremity joint dynamics during wheelchair mobility - Schnorenberg, Alyssa J.; Slavens, Brooke A.; Wang, Mei; Vogel, Lawrence C.; Smith, Peter A.; Harris, Gerald F. (Journal of biomechanics, 2014)
Pediatric manual wheelchair users (MWU) require high joint demands on their upper extremity (UE) during wheelchair mobility, leading them to be at risk of developing pain and pathology. Studies have examined UE biomechanics during wheelchair mobility in the adult population; however, current methods for evaluating UE joint dynamics of pediatric MWU are limited. An inverse dynamics model is proposed to characterize three-dimensional UE joint kinematics and kinetics during pediatric wheelchair mobility using a SmartWheel instrumented handrim system. The bilateral model comprises thorax, clavicle, scapula, upper arm, forearm, and hand segments and includes the sternoclavicular, acromioclavicular, glenohumeral, elbow and wrist joints. A single 17 year-old male with a C7 spinal cord injury (SCI) was evaluated while propelling his wheelchair across a 15-meter walkway. The subject exhibited wrist extension angles up to 60°, large elbow ranges of motion and peak glenohumeral joint forces up to 10% body weight. Statistically significant asymmetry of the wrist, elbow, glenohumeral and acromioclavicular joints was detected by the model. As demonstrated, the custom bilateral UE pediatric model may provide considerable quantitative insight into UE joint dynamics to improve wheelchair prescription, training, rehabilitation and long-term care of children with orthopedic disabilities. Further research is warranted to evaluate pediatric wheelchair mobility in a larger population of children with SCI to investigate correlations to pain, function and transitional changes to adulthood.